Pembuatan Katalis Padat ZrO2/Al2O3 untuk Produksi Biodiesel dari Minyak Jarak - Syamsuddin, Yanna; Husin, Husni (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2010)
Biodiesel is one of the alternative energy to replace petroleum diesel. Biodiesel is produced by transesterification of vegetable oil into alkyl ester and glycerol as by-product. The vegetable oil based put biodiesel as a renewable and environmentally friend energy source. Research on making of solid catalyst ZrO2/Al2O3 for biodiesel production from jatropha oil has been done. The catalysts were prepared by impregnation method with different amount of Zr (2, 5, 15, and 20%) and the components were characterized by using XRD. Transesterification reaction was done by reacting jatropha oil with methanol and catalyst with the ratio of oil to methanol of 1:6, reaction temperature of 60oC, and reaction time of 3 hours. Biodiesel produced were analyzed for their yield and composition using GC-MS. The biodiesel products were also characterized for their viscosity, density, acidic and saponification value. Characterization of catalysts showed that components of synthesized ZrO2/Al2O3 were ZrO, ZrO2, and Al2O3. The highest yield of biodiesel produced was resulted from transesterification reaction using catalyst with 2% Zr. GC-MS results showed that methyl esters of biodiesel produced confirmed with fatty acids in jatropha oil with methyl oleic is the highest. Characteristic of the biodiesel has met the quality standard of ASTM, prEN and SNI.Keywords: biodiesel, katalis, minyak jarak, ZrO2/Al2O3